An Analysis of School Principals' Course Supervision Activities in Regard of Instructional Leadership - Köksal Buran; Serkan Koşar (Anı Publishing, 2019)
It has been aimed to evaluate the course supervision activities of school principals in the context of instructional leadership. This study is designed in a qualitative research method, in case study design. The most prominent feature of the qualitative case study is the in-depth study of the identified subject. Maximum diversity and criterion sampling methods were used for research purpose sampling methods. A working group consisting of 15 school principals performing in private educational institutions, kindergartens, primary schools, secondary school and high school in the districts of Çankaya, Yenimahalle and Mamak with regard to the problem determined was formed. In the study, a semi-structured interview form was used to determine the opinions of school principals on course supervision. As a result of the research, it was concluded that the course audits should be realized by school principals in order them to better define the school and the teacher and to ensure effectiveness in the supervision. Regulation changes related to course audits were welcomed by school principals. The headmaster should conduct the supervision in a positive way and constitute a role model for the teacher. He should constitute a common vision as a teaching leader and motivate all the teachers to reach the designated vision.